The SME in a Globalized Economy. Challenges of the Albania's SME in the Optic of Small Business Act - Xhafka, Eralda; Avrami, Elidon (European Journal of Economics and Business Studies, 2015)
In the context of globalization, SMEs tends to consolidate and the question of how SMEs manage the competition is intriguing. Besides larger competitors with visible, physical premises, other processes related to globalization are presenting SMEs with both opportunities and threats. The next 5 years are an important benchmark for a number of EU political processes that indirectly effect the well-being of the SME´s. SBA is a bright idea how to follow-up and reinvigorate the Lisbon Strategy so that the continuing efforts of Entrepreneurs are focused on the real reforms that they desperately need to implement. All SME face rigid labor markets that keep a large part of the work-force outside the labor market. They have tax systems that not only discourage innovation and creativity but also actually destroy incentives and risk-taking. Entrepreneurs need secure and stable rules. Otherwise they might become disillusioned about the European project as a whole. They know that closer integration can give them increased competitiveness, growth and jobs. They must therefore be able to continue to believe in Europe as their natural platform for trade and investment. The Small Business Act, launched by the European Commission, identifies the right priorities to unleash the potential of the SME. This paper analysis the characteristic of the Albania SMEs, advantages and disadvantages in relation to Globalization and present the solution of the ten principles of SBA as a way forward to improve their performance.
Keywords: Globalization, SME, Small Business Act, European Commission, Albania